Germination and field emergence in osmotic and solid matrix priming in onion (Allium cepa) - SINGH, PUNEET KUMAR; PANDITA, V K; TOMAR, B S; SETH, RAKESH (The Indian Journal of Agricultural Sciences, 2014)
Solid matrix priming for 24 hr significantly improved seed germination (81.6%) as compared to 12 hr, 36 hr or 48 hr duration. A priming duration of 24 hr gave maximum speed of germination (16.95) while priming duration of 48 hr gave minimum value for speed of germination. No significant differences in speed of germination were found at different temperatures. The interaction effect of priming duration and temperature revealed that solid matrix priming for 24 hr at 20°C is optimum for obtaining maximum speed of germination (17.34). Maximum vigour index I (848.1) was obtained in solid matrix primed seeds for 24 hr duration at 20°C temperature. Osmopriming using PEG 6000 (–1.5MPa) significantly improved seed germination (78%). With increase in priming duration from 2 days to 6 days, there was significant decrease in germination. Osmopriming at –1.0 MPa PEG potential significantly improved speed of germination (7.78) as compared to –0.5 and –1.5MPa potential. The interaction effect of PEG potential and priming duration revealed that osmopriming for 2 days at –1.0 MPa PEG potential gave maximum speed of germination (8.35) over all other treatment combinations. Osmopriming using PEG 6000 (–1.0MPa for 2 days) improved germination by 14.3 percent and field emergence by 13 percent over control. Solid matrix priming for 24 hr at 20oC also improved germination by 13 percent and field emergence by 11.3 percent over control. These results indicate that osmopriming and solid matrix priming can be effectively employed to prime onion seeds for improved field performance.